The Role of Specific Elements Social Entrepreneurship in Health - Lucia Durac; Liliana Mihaela Moga (Risk in Contemporary Economy)
Health was, is and will remain an area of interest, complex and of overwhelming importance in any country, and that is why it is necessary to adopt policies to reduce health disparities, considering the fact that the Romanian population has predominantly low incomes and average. The research carried out highlights the fact that mental health at the global level remains one of the main disabilities, and as this aspect becomes more aware, resources must be identified to which all those who need access can have access, in order to eliminate discrimination, stigma and for the integration of the affected person in society Studies show that before the Covid-19 pandemic over 70% of those who needed therapy and specialized mental health services did not have access to this care (Wainberg, ML, Scorza, P., Shultz, JM et al.) . the percentage rising to 93% once the pandemic is over. In Romania, the access of people with mental disorders who have medium incomes to specialized medical and therapeutic assistance is limited, and those who have low incomes do not have access to care. Hence the need to support and promote entrepreneurial initiatives that most often support public health systems, which are often underfunded. Social entrepreneurs, those who transform innovative ideas into effective services, also called "agents of change" are the ones who must find solutions to social problems, through appropriate levers, to obtain the greatest impact with the least effort. Social entrepreneurs are involved, empathetic, they apply innovative strategies to generate solutions to the problems around them and even more so, they get involved without necessarily waiting for the help of others. Thus, through social entrepreneurial ideas, with passion and involvement, progress can be made in the field of mental health, bringing major improvements in the lives of those involved. This research wants to highlight the role of social entrepreneurial structures in supporting people affected by mental health problems and the beneficial effects of the activities developed by these structures, on improving the physical and mental state. The research carried out confirms the major role that social enterprises founded following an innovative idea in fields such as health, sports, recreational and entertaining activities, have on people affected by mental health problems, there are notable results in this regard.